Impacts of flood disaster on sustainable national development in Ibadan North Local Government, Oyo State (2014)
The paper investigated impacts of flood disaster on sustainable national development in Ibadan North Local Government Area of Oyo State. Three research hypotheses were postulated and tested at 0.05 alpha level. The research design adopted for the study was survey type. Through purposive randomly sampling techniques, a sampled population of three hundred and twenty residents was used. Data were collected with the use of researcher’s structured questionnaire already validated by two experts in the field of Health Promotion and Environmental Health Education and Geography. Pilot testing was conducted using split half method. A reliability coefficient of .78r was obtained. Demographic data collected were analyzed with the aid of frequency counts and simple percentage while the postulated hypotheses were tested with the use of inferential statistics of Chi-square. The results of the study revealed that flood disaster had significant impact on socio-economy, agricultural production and environment. Based on these findings, the researcher recommends that residents are advised to avoid indiscriminate dumping of refuse as this could result into flood disaster and government at all levels should embark on public drainage and bridge construction so as to pave way for water during heavy rainfall.